An In vivo Comparative study to evaluate the colour stability of porcelain laminate veneers Fabricated by two Different techniques (CAD/CAM, Hot Press) - بهرلي ناصر; سليمان حيدر (Latakia University Journal -Medical Sciences Series, 2021)
Background and objective : the color stability of the porcelain veneers plays an essential rule of the aesthetic side durability of porcelain veneers. The color stability of porcelain veneers was studied in the laboratory and only with regard to resin cement mainly, but clinically, we did not find studies evaluated the color stability of thin porcelain veneers of all kinds. This study aims to evaluate the colour stability of porcelain laminate veneers Fabricated with the most common two techniques (CAD/CAM,Hot Press). Materials and methods: A sample of 10 patients whose anterior incisors indicated for treatment with 32 thin porcelain veneers as follows: the first group contained 5 patients who treated with 16 porcelain veneers fabricated with (IPS e.max CAD) technique, and the other group contained 5 patients who treated with 16 porcelain veneers fabricated with (IPS e.max Press) technique. Color was evaluated with a spectrophotometer Compact Vita Easyshade . ∆a*, ∆b*, and ∆L* were calculated between the first and subsequent measurements at 24 hours and at 6, 12, and 24 months after cementation. Then CIE Lab (∆E ab) were used to quantify color alteration. Results: NO Statistically significant differences were observed of means ∆E*ab values in both techniques (CAD/CAM,Hot Press) after 6, 12,24 months at p≤0,05. The threshold for clinically acceptable color changes ∆E*ab≤ 3.5 was found for both techniques (CAD/CAM,Hot Press) after 6,12,24 months . Conclusion:. The color stability of both (CAD/CAM,Hot Press) Veneers was clinically achieved for all evaluated periods.